2015
DOI: 10.3892/ijo.2015.3225
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 stimulates aerobic glycolysis by regulating PFKFB3 at early stage of colorectal cancer

Abstract: Abstract. Chronic inflammation is a well-known etiological factor for colorectal cancer (CRC) and cancer cells are known to preferentially metabolize glucose through aerobic glycolysis. However, the connection between chronic inflammation and aerobic glycolysis in the development of CRC is largely unexplored. The present study investigated whether interleukin-6 (IL-6), a pro-inflammatory cytokine, promotes the development of CRC by regulating the aerobic glycolysis and the underlying molecular mechanisms. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…heterogeneity among the types of cancer may explain these differences. In addition, IL-6 overexpression can accelerate LNM in cervical cancer, colorectal cancer and lung cancer by stimulating cell proliferation, migration or EMT (36)(37)(38). This is consistent with the results from the present study, which demonstrated that IL-6 was upregulated and enriched in the PI3K-Akt signaling pathway, indicating that IL-6 may promote LNM progression in TC.…”
Section: Discussionsupporting
confidence: 92%
“…heterogeneity among the types of cancer may explain these differences. In addition, IL-6 overexpression can accelerate LNM in cervical cancer, colorectal cancer and lung cancer by stimulating cell proliferation, migration or EMT (36)(37)(38). This is consistent with the results from the present study, which demonstrated that IL-6 was upregulated and enriched in the PI3K-Akt signaling pathway, indicating that IL-6 may promote LNM progression in TC.…”
Section: Discussionsupporting
confidence: 92%
“…This is therefore a control point in the pathway and PFKFB3 is an acknowledged key regulator of glycolysis. Among the factors that trigger activation of PFKFB3 are inflammatory mediators; for example, IL‐6 increased PFKFB3 mRNA in mouse embryonic fibroblasts and cancer cell lines and several studies have indicated that LPS triggers PFKFB3 in macrophages . Few studies have investigated factors that drive PFKFB3 in microglia but we have reported that IFNγ alone and also LPS+Aβ exert this effect.…”
Section: Discussionmentioning
confidence: 87%
“…IL-6 is a critical tumour promoter during early CRC tumourigenesis[20]. In mice with colitis-associated cancer, anti-IL-6 receptor antibody treatment reduced the incidence of colitis-associated cancer (CAC) by decreasing the expression of key genes in aerobic glycolysis[23]. In an experimental CAC mouse model, researchers found that the expression levels of IL-6 protein were gradually increased after the induction of dysplastic lesions over time.…”
Section: Discussionmentioning
confidence: 99%